Improvement of Speed Running Through Plyometric Exercises - Rigerta, Selenica; N, Quka; E, Selenica (Arena-Journal of Physical Activities, 2020)
Introduction: Sports performance and all physical exercise depend on the coordination of skeletal muscle activation by providing the strength and power that translates into the ability of the movement. Today, it is generally accepted that sprint performance, like endurance performance, can improve considerably with training. Strength training, especially, plays a key role in this process. Aim: The purpose of the study was to find out how the plyometric exercises influence the development of elastic force improving stages of speed running for the 30m; 30-60m and 60m. Methodology: This literature was selected by different research sectors that are based on the internet like â€žJab Refâ€ â€žPubMedâ€ â€žGoogle Scholarâ€ â€žMedlineâ€ â€žSports Discussâ€. Our study is focused on 39 subjects, students of the â€žSports University of Tiranaâ€ Students were separated into 2 groups. The average age of the participants was 19-20 years. In our study we involve 1(one) experimental groups, respectively this group was trained with plyometric exercises and the Control group. In order to collect data for contact time, and speed running is used these measuring instruments Brower Timing Systems 2010, Leonardo Mechanograph Â® GRFP standard variant of STD. Results and conclusion: The experimental group showed improvement in running speed for the 0-30m distance with 4.7% m/sec for average group values. Compared to the Control group, the results for this distance indicated for sigâ‰¤0.05. For the 30-60m distance the speed improved by 3.96% m/sec for the average value in the group. Compared to the Control group the results for this distance showed values of sig=0.11 not significant for sigâ‰¤0.05. For the 60m distance, the speed was upgraded to 3.53% m/sec for average group values. Compared to the Control group, the results for this distance showed sig=0.08 for sigâ‰¤0.05. In control group, the contact time indicator from the height 40cm showed correlation with running speed for the three (3) measured distances where for 0-30m with r = -0.605; 30-60m with values of r = -0.540 and 60m with values of r = 0.566. Based on the above results, the plyometric method applied in the experimental group showed more correlation between contact time by h=40cm and the running speed on acceleration phase 0-30m.